2012
DOI: 10.1186/1746-6148-8-162
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validity of outcome pain measures in naturally occurring canine osteoarthritis

Abstract: BackgroundThe conceptual validity of kinetic gait analysis and disability outcome assessment methods has guided their use in the assessment of pain caused by osteoarthritis (OA). No consensus on the best clinical methods for pain evaluation in canine OA exists, particularly, when evaluating treatments where a smaller treatment effect is anticipated than with pharmacological pain killers. This study thus aimed at determining the technical validity of some clinical endpoints on OA pain in dogs using the green-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…Currently, no standardized canine trotting velocity range is available. More than ten unique trotting velocity ranges, narrow and wide, have been used in veterinary trials to-date (Rumph et al, 1993; Borer et al, 2003; Ballagas et al, 2004; Lopez et al, 2006; Havig et al, 2007; Voss et al, 2008; Malek et al, 2012; Rialland et al, 2012; Brown et al, 2013; Fahie et al, 2013). The variance effects of these velocity ranges on GRF in a heterogeneous population have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, no standardized canine trotting velocity range is available. More than ten unique trotting velocity ranges, narrow and wide, have been used in veterinary trials to-date (Rumph et al, 1993; Borer et al, 2003; Ballagas et al, 2004; Lopez et al, 2006; Havig et al, 2007; Voss et al, 2008; Malek et al, 2012; Rialland et al, 2012; Brown et al, 2013; Fahie et al, 2013). The variance effects of these velocity ranges on GRF in a heterogeneous population have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Dogs with OA may show clinical signs of limping, stiffness of joints, immobility, crepitus, periarticular swelling, and lameness. Pain associated with inflammation appears to be the most serious sign of OA [3,[11][12][13][14][15][16]30]. As stated in the introduction, pathophysiology of OA is very complex due to involvement of multiple factors [18,[20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, more than 20% of the adult and 80% of the geriatric dog population in the US (>80 million) suffer from OA [3]. A number of factors (injury/trauma, aging, excessive or lack of exercise, genetic predisposition, poor nutrition, obesity, and environmental factors) can contribute to OA in dogs [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has been suggested that accelerometers are measuring a different outcome that may not be related to established outcomes (Rialland et al, 2012), weak correlations may also be caused by variability in data collection. Specifically, inter-device variability and collar tightness may affect activity counts.…”
Section: Introductionmentioning
confidence: 99%